Theorico-Game Approach for Interaction of Corporate Center and Divisions in Companies - A. A. Kulikov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article describes variants of applying mathematic modeling by using the theory of games to resolve concrete corporate problems with regard to high level of competition on human capital market, including elaboration of strategy of managing cooperation between corporate center and division teams. On the basis of theorico-game method the author proposes a variant of 3D payment matrix meant for searching for optimum solutions in contradictions between the corporate center and division. As a third axis the author proposes velocity of decisionmaking that can provide identification of the needed strategy within the necessary interval of time. The article described 18 variants of conflict settlement by finding alternative steps of two participants as well as winnings and losses being the result of choosing each of the strategies.